Estudos de anisotropia sísmica causada por fraturas verticais através do uso de dados multicomponente - Silva, Eliene Bezerra Simão da (2017)
Anisotropy caused by fractures is a major cause of uncertainties in projects for borehole perforation, since fractures may become pathway for fluid flow or even create barriers during oil production. This issue can be dealt with via seismic anisotropy investigation to map fracture set orientation and density in subsurface, impacting on borehole placement and direction for the field development. This study aims to develop a software (analize) for this type of seismic anisotropy analysis of multicomponent data. Analize is validated through anisotropy investigation in modeled synthetics. The main products of its analysis are the fracture azimuths and the degree of anisotropy. Qualitative and quantitative results are coherent with the model, showing that the computational code is a powerful tool for anisotropy investigation. 4C ultrasonic physical modeling seismic surveys are performed to simulate the Ocean Bottom Nodes (OBN) method and to investigate the existence of converted-waves PS anisotropy from the water-bottom. Carbonate rock properties were measured and their reflection and transmission coefficients for the model interfaces were studied. The median connected porosity for the carbonate in the model was estimated by the fluid saturation. P-wave and the converted PS-wave have shown great imaging of the cave formation and PS-wave has presented azimuthal variation of ∆t, suggesting possible azimuthal anisotropy. Those indicators were later investigated by analize with full-azimuth data (2C x 2C) and confirmed axis of symmetry shown previously.